Development of a PBL-Based E-LKPD Assisted by the wizer.me Website on Buffer Solution Material for Phase F Senior High School Students - Suci Ramadani; Desy Kurniawati (MO.RI Publishing, 2026)
This study is a research and development (R&D) study aimed at producing an electronic student worksheet (E-LKPD) based on Problem-Based Learning (PBL) assisted by the Wizer.me website on the topic of buffer solutions. The development model employed was the 4-D model, comprising the define, design, develop, and disseminate stages; however, this study was limited to the develop stage. The research instruments included interview guidelines, validation sheets, teacher practicality questionnaires, and student response questionnaires. The research subjects consisted of three chemistry lecturers from FMIPA UNP, two chemistry teachers from SMA Pertiwi 1 Padang, and Phase F students of SMA Pertiwi 1 Padang in the 2025/2026 academic year. The data collected were primary data analysed through validity and practicality tests. The expert validity test yielded an average Aiken's V index of 0.91, categorised as valid. The practicality test results indicated mean scores of 96% from teachers and 90% from students, both categorised as very practical. Based on these findings, it can be concluded that the developed PBL-based E-LKPD assisted by Wizer.me is valid, highly practical, and feasible for use as a chemistry learning medium on buffer solution material.